2016
DOI: 10.1080/21645515.2016.1160178
|View full text |Cite
|
Sign up to set email alerts
|

Is HPV vaccination in pregnancy safe?

Abstract: Millions of doses of HPV vaccine have been administered globally. Inadvertent administration of HPV vaccine during pregnancy occurs given that the main recipients of the vaccine are fertile young women, who might be unaware of their pregnancy at the time of their vaccination. To investigate the subject of HPV vaccine and pregnancy , the databases of PubMed and Embase were searched to find the relevant literature published in English within the last 10 y. Most of the evidence pertaining to fetal adverse events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…Safety of HPV vaccines in pregnancy or immediately pre-conceptually has been reviewed ( 230 ). The HPV vaccination concerns were not only the maternal safety, but also (and more) on the teratogenicity and other fetal adverse events (AEs) following HPV vaccination, including spontaneous miscarriage, preterm birth, congenital malformations, and fetal decease.…”
Section: Hpv Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Safety of HPV vaccines in pregnancy or immediately pre-conceptually has been reviewed ( 230 ). The HPV vaccination concerns were not only the maternal safety, but also (and more) on the teratogenicity and other fetal adverse events (AEs) following HPV vaccination, including spontaneous miscarriage, preterm birth, congenital malformations, and fetal decease.…”
Section: Hpv Diseasementioning
confidence: 99%
“…For the fetal safety, none of the studies reported a significant increased rate of spontaneous abortion and other fetal outcomes in overall subgroup analyses (e.g., age, interval of time of conception and nearest vaccination, number of vaccinations) compared with controls. The conclusion was the risk of AEs during pregnancy is unrelated to HPV vaccination before or during pregnancy ( 230 ).…”
Section: Hpv Diseasementioning
confidence: 99%
“…Comments Bearing in mind the paucity of research in his area, the authors should consider citing the review of adverse outcomes of pregnancy in association with HPV ( Bonde U, et al The potential role of HPV vaccination in the prevention of infectious complications of pregnancy 1 .The authors should consider alluding to the safety or otherwise of HPV vaccination in pregnancy ( Bonde U, et al Is HPV vaccination in pregnancy safe? 2 ). The study by Bruinsma (cited as Reference 14) had significant flaws and these were highlighted in the subsequent correspondence(Lamont RF, Sarhanis P. Precancerous changes in the cervix and risk of subsequent preterm birth 3 ).…”
mentioning
confidence: 99%
“…In pregnancy, the true safety of the HPV vaccination has not yet been established through randomized controlled trial. Hence, the HPV vaccine administration to the pregnant women has not yet been approved [132].…”
Section: Hpv Vaccination During Pregnancymentioning
confidence: 99%